Optimization of a Management Algorithm for an Innovative System of Automatic Switching between Two Photovoltaic and Wind Turbine Modes for an Ecological Production of Green Energy - Yahya Lahlou; Abdelghani Hajji; Mohammed Aggour (International Journal of Renewable Energy Development, 2023)
Today, renewable energy and energy efficiency are key to limiting global warming and preventing the dangerous effects of climate change. The biggest problem with conventional solar and wind turbine systems is the intermittency of electrical power generation. Even if these two energy sources can be complementary, the space occupied by these hybrid systems remains very important. This work proposes an improved management algorithm for a patented transformable photovoltaic-wind system, which mainly uses two flexible photovoltaic panels which are automatically deformed by an electromechanical system from the planar shape to the semi-cylindrical shape of the Savonius wind turbine blades. When weather conditions change, this system switches to eco-friendly photovoltaic (PV) or wind turbine (WT) mode, allowing a good total power generation from two solar power sources or wind turbine power. The contribution brought for this work relates to the realization and the improvement of the management algorithm to determine a better change to the mode PV or the mode WT. The operation test was simulated in 8760 hours for the year 2021. This developed algorithm allows several theoretical calculations of the power produced from solar radiation and wind speed data, thereafter the algorithm compare and determines the overall power and selects the optimal PV or WT mode. In this study, the overall power generated by the invented system produces more electricity per hour, the power Pt increases by 75.55% compared to the power Pwt, and also the power Pt increases by 68.15% compared to Pvp power.